2017
DOI: 10.1063/1.5001185
|View full text |Cite
|
Sign up to set email alerts
|

Significant increase of quantum efficiency of green InGaN quantum well by realizing step-flow growth

Abstract: Two-dimensional (2D) island morphologies have been widely reported for green light-emitting InGaN quantum well (QW) layers, but the step-flow morphology has not been obtained for a green InGaN QW layer to date. In this Letter, we first investigate the cause of the 2D island morphology of green InGaN QWs via a comparison study with blue InGaN QWs. The short diffusion lengths of adatoms at low growth temperatures were found to be the cause of the 2D island morphology for the green InGaN QW. Step-flow growth of g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 29 publications
1
3
0
Order By: Relevance
“…Regarding the rate of increase in IQE in the green region, its value increases at an unparalleled rate 29 -33 . Figure 4a shows the IQE obtained in this study and those of other groups reported recently [23][24][25][26] . The improved IQE of SQW and 3QW are plotted as blue, green, and red stars, respectively.…”
Section: Mechanism Of Signi Cant Pl Enhancements With Oxide Thin Lms ...supporting
confidence: 67%
“…Regarding the rate of increase in IQE in the green region, its value increases at an unparalleled rate 29 -33 . Figure 4a shows the IQE obtained in this study and those of other groups reported recently [23][24][25][26] . The improved IQE of SQW and 3QW are plotted as blue, green, and red stars, respectively.…”
Section: Mechanism Of Signi Cant Pl Enhancements With Oxide Thin Lms ...supporting
confidence: 67%
“…19,20 Until now, the growth of thick InGaN layers has not been extensively studied because of the synthesis challenges arising from the phase separation and surface control. 21,22 Pantzas et al reported that insertions of thin GaN interlayers during InGaN growth can suppress the phase separation and improve the surface quality. However, the reported root-mean-square roughness of 3.1 nm still seems too high for the subsequent QW growth.…”
mentioning
confidence: 99%
“…A reduced QCSE leads to an increased overlap between electron and hole wave functions, and a much higher spontaneous emission rate can be achieved compared to the same InGaN QWs grown on a GaN buffer layer. , Even et al studied the growth dependence of InGaN QWs on the indium content in InGaN pseudosubstrates and found an enhanced indium incorporation into the QWs due to the reduced indium pulling effect . This enables the growth of green and red InGaN QWs at a higher temperature for a higher quality. , In addition, a higher hole concentration is expected in InGaN as a result of a lower activation energy for the p-type doping compared to GaN. , Until now, the growth of thick InGaN layers has not been extensively studied because of the synthesis challenges arising from the phase separation and surface control. , Pantzas et al reported that insertions of thin GaN interlayers during InGaN growth can suppress the phase separation and improve the surface quality. However, the reported root-mean-square roughness of 3.1 nm still seems too high for the subsequent QW growth .…”
mentioning
confidence: 99%
“…Both NAs and RAFs manifest themselves in features of the surface morphology [14,15]. According to [13,16], these features are characterized by the degree of nanomaterial disorder (DND). So, in further discussion regarding DND, we will understand it as the nanoarrangement of domain structure, RAFs, and the presence of local regions with disrupted stoichiometry of alloy composition.…”
Section: Introductionmentioning
confidence: 99%